Arqueologia da arquitetura e tectônica: abordagens integradas e seu impacto no processo de restauração na Casa de Câmara e Cadeia de Mariana-MG - Adriano Luís Furini de Souza (2024)
In this work, I seek to analyze the restoration process of the Casa de Câmara e Cadeia de Mariana, through theoretical and methodological subsidies from the Archeology of Architecture (AA) end Tectonics. In this way, the aim is to understand this object from a holistic perspective, considering not only the building itself but also the sociological, artistic, philosophical, anthropological, political and cultural aspects that motivated any changes to the building. It should be noted, therefore, that the main objective of this work concerns the examination of the Câmara e Cadeia de Mariana building as an archaeological artifact and tectonic element, in which we embrace a transdisciplinary perspective, with a view to supporting decision-making in the restoration process. In this way, we understand that our work can contribute, to some extent, to the cultural and memorialist recovery of data embodied in the historicity of the building itself, as well as to methodological renewal, by deepening debates related to the Archeology of Architecture and, especially, in the restoration process. This time, and with the aim of expanding AA's activities, we seek, through daily experiences on the construction site, to systematize a specific method for restoration. Therefore, through this case study, we aim to evaluate the applicability of Architectural Archeology in the process of restoring the Mariana Town Hall and Prison, emphasizing its contributions or possible discrepancies, in an effective association of theory with practice.